Program Pengembangan Usaha Produk Intelektual Kampus “Kantor Konsultan Bisnis, Akuntansi dan Pajak” - Fadrul Fadrul; Sarli Rahman; Sudarno; Yusrizal (Universitas Lancang Kuning, 2020)
Every college must have a business unit that is able to seek funding apart from students. One of the universities that has a business unit is the Institut Bisnis dan Teknologi Pelita Indonesia. The business unit that is carried out is the Business, Accounting and Tax Consultant Office with services offered namely business consulting, accounting and finance and taxation. Some of the clients that have been handled by the consultant team are Raso Stiujuah Restaurant and BUMDes Sialang Kubang. The method used is that the consultant team looks for the root of every problem faced by the client, then provides the best solution for the client. For Raso Situjuah Restaurant, to survive the changing business world situation and the current pandemic atmosphere is to create frozen products and with a digital-based marketing system. Meanwhile, for BUMDes Sialang Kubang, in managing the BUMDes, personal and institutional strengthening is needed in the form of Standard Operational Procedures (SOP) and the availability of an accurate and accountable information system.